Academic Publication of Anesthesiology From a Bibliographic Perspective From 1999 to 2018: Comparative Analysis Using Subject-Field Dataset and Department Dataset - Chen, Sy-Yuan; Wei, Ling-Fang; Huang, Mu-Hsuan; Ho, Chiu-Ming (Frontiers in Medicine, 2021)
Background: Publication activity in the field of anesthesiology informs decisions that enhance academic advancement. Most previous bibliometric studies on anesthesiology examined data limited to journals focused on anesthesiology rather than data answerable to authors in anesthesia departments. This study comprehensively explored publication trends in the field of anesthesiology and their impact. We hypothesized that anesthesiology’s bibliometric scene would differ based on whether articles in the same study period were published in anesthesiology-focused journals or were produced by authors in anesthesia departments but published in nonspecialty journals. Methods: This cross-sectional study used bibliometric data from the Science Citation Index Expanded database between 1999 and 2018. Two datasets were assembled. The first dataset was a subject-dataset (articles published in 31 journals in the anesthesiology category of InCites Journal Citation Reports in 2018); the second dataset was the department-dataset (articles published in the Science Citation Index Expanded by authors in anesthesia departments). We captured the bibliographical record of each article in both datasets and noted each article’s Institute for Scientific Information code, publication year, title, abstract, author addresses, subject category, and references for further study. Results: A total of 69,593 articles were published—cited 1,497,932 times—in the subject-dataset; a total of 167,501 articles were published—cited 3,731,540 times—in the department-dataset. The results demonstrate differences between the two datasets. First, the number of articles was stagnant, with little growth (average annual growth rate = 0.31%) in the subject-dataset; whereas there was stable growth (average annual growth rate = 4.50%) in articles in the department-dataset. Second, only 30.4% of anesthesia department articles were published in anesthesiology journals. Third, journals related to ‘pain’ had the lowest department-subject ratio, which was attributable to a large portion of non-anesthesia department researchers’ participation in related research. Conclusions: This study showed that articles published in anesthesiology-focused and nonspecialty journals demonstrate fundamentally different trends. Thus, it not only helps researchers develop a more comprehensive understanding of the current publication status and trends in anesthesiology, but also provides a basis for national academic organizations to frame relevant anesthesiology development policies and rationalize resource allocation..